Utilization of screening services on cervical cancer and associated factors among female health workers in Addis Ababa, Ethiopia - Achamyelew Melaku; Shiferaw Negash Abebe; Sofanit Haile (PLoS ONE, 2025)
Background Cervical cancer is the fourth most common cancer among women worldwide and the second most common cancer in women in Ethiopia with the disease claiming the lives of more than 340, 000 women globally in 2020. A well organized and arranged screening is one of the key intervention strategies in the reduction of the incidence and mortality from the disease. Healthcare workers, being the front line in health delivery system, are expected to play a critical role in cervical cancer screening. This being the fact on the ground, the gap on the cervical cancer screening service utilization and the factors influencing it among female health workers in Ethiopia is not well elucidated. We aim to explore the magnitude of the screening uptake and associated factors among female healthcare providers in Addis Ababa, Ethiopia. Methods Institution-based cross-sectional study using stratified multi-stage sampling technique was done from June 05 to July 05, 2023 among female health workers in Addis Ababa. The data was collected using a structured self-administered questionnaire. Descriptive statistics like mean, median, and proportion were used to summarize the data. Bivariable regression analysis was used to measure the association between the dependent and independent variables, while multivariable regression analysis was used to determine the independent associations. Variables with P-value≤ 0.25 on bivariable model were entered into a multivariable logistic regression model. Odds ratios with 95% confidence intervals (CIs) were computed to measure the strength of association, and statistical significance was declared at P< 0.05. Results A total of 432 study participants were enrolled in the final analysis with the response rate of 100%. Out of the total participants, 243 (56.3%) were nurses, and 183 (42.4%) were of age 30 years and above. In this study, only 19.4% (84/432) and 31.2% (57/183) among all participants and the targeted groups (age ≥30 years), respectively, have utilized the screening services. The lack of attention was the main reason identified hindering the screening service utilization (32.5%) while the promoter factors being awareness about screening methods (48.8%) and physician recommendation (26.2%). On Multivariable model; participant age ≥30 years (AOR=1.6, 95%CI1.15–3.37), being married (AOR=6.1, 95%CI 2.42–15.06), and working in cervical cancer screening units (AOR=3.7, 95%CI1.01–12.12), respectively had an independent association with the screening service utilization. Similarly, the study participants knowledge of the etiology, knowledge of cigarette smoking as risk factor, and visual inspection with acetic acid as screening method had shown an independent association with screening service utilization, (AOR=1.6, 95%CI=1.01–12.12), (AOR=4.1, 95%CI1.68–9.76), (AOR=14.2, 95%CI3.77–53.32), respectively. Conclusion The low screening services utilization among the targeted age group of female health workers is alarming. The lack of attention and feeling of healthy were hindering factors among those not yet screened, while those screened were motivated by the awareness created and physician recommendation. Continual awareness creation and training of female healthcare providers on cervical cancer and its screening is recommended to improve the screening service uptake by the women in the population.